Safety and Effectiveness of Percutaneous Ultrasound-Guided Galvanic Current in Tunnels of Patients with Hidradenitis Suppurativa: A Pilot Study - Alberto Soto-Moreno; Carlos Cuenca-Barrales; Salvador Arias-Santiago; José Antonio García-Vidal; Francesc Medina-Mirapeix; Alejandro Molina-Leyva (Adis, Springer Healthcare, 2024)
Abstract Introduction The recurrent nature of hidradenitis suppurativa (HS), even under maintained systemic treatment, makes it necessary to have effective local treatments; however, the response to these therapies is variable (44-81%). The application of galvanic current (GC) has demonstrated its utility in humans in treating lesions structurally similar to those of HS. With this background, the main objective of this study was to evaluate the efficacy and safety of ultrasound-guided percutaneous GC in inflamed and/or draining tunnels of HS. Methods This was an open study (one-way repeated measures design over time). Patients were evaluated at 4 and 12 weeks after receiving GC. A combined clinical response at week 12 (absence of suppuration/inflammation on examination and clinical interview) was considered the principal variable of efficacy. Adverse effects potentially associated with GC were reported by telephone and at each visit. Results Twenty-six patients were included, with a male/female ratio of 5:8. The mean age was 35.84 (13.14) years. At 12 weeks after the administration of GC, a complete response was achieved in 77% (20/26) of the treated lesions. No serious adverse effects were observed, and the mean procedural pain assessed by the numeric rating scale was 0.03 (0.2). Conclusion GC has proven to be effective and well tolerated in inflamed and draining tunnels of patients with HS.